Village Autonomy in Facing Village Independence - Yamin, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims: 1) to describe the concept of Village Autonomy, 2) to describe Independent Villages, 3) to describe Village Autonomy, village autonomy towards village independence. The research method used is descriptive qualitative research with a library research approach. The results of this research are 1) The implementation of Village Autonomy is genuine, complete and complete autonomy and is not a gift from superior or supra-village government, on the contrary, the government is obliged to respect the original autonomy of the village; 2) The independent village concept is a rural development pattern based on an integrated concept starting from the input subsystem, primary production subsystem, product processing subsystem, marketing subsystem, and support services subsystem; village autonomy towards village independence is carried out through the development of rural areas to be targeted and appropriate with what is in the interests of village communities, planning mechanisms for implementing village development must be carried out starting from the bottom.